PERAN GURU DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V MI NEGERI 7 DEMAK - Usna, Eva Syafa'atul; Kinesti, Rakanita Dyah Ayu (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to describe the role of teachers in improving mathematics learning achievement of fifth grade students at MI Negeri 7 Demak and identify supporting and inhibiting factors. The approach used is descriptive qualitative with interview, observation, and documentation methods. Interviews were conducted with teachers, principals, and two students with different achievements. Participatory observation was conducted in class, and data analysis used the Miles and Huberman model and thematic analysis. The results of the study indicate that teachers have an important role as motivators, facilitators, and evaluators. Teachers apply varied learning strategies, provide ongoing motivation, and carry out systematic evaluations to increase students' interest and understanding of mathematical concepts. Individual approaches and the use of innovative learning methods have also proven effective in improving student achievement. However, this study identified obstacles such as limited facilities and infrastructure and high administrative burdens on teachers. The conclusion of the study emphasizes that optimizing the role of teachers can be achieved through increasing competence, supporting facilities, and collaboration between teachers, students, and parents as the main steps in improving students' mathematics learning achievement.